Prescribing Trends of Analgesics Used in Postoperative Patients in a Surgical Unit of Enam Medical College Hospital (Bangladesh Journal of Physiology and Pharmacology, 2010)
The present study was conducted to evaluate the prescribing trends of analgesics used in the postoperative patients in a surgical unit of Enam Medical College Hospital. Treatment records of 180 patients, who underwent surgery in Enam Medical College Hospital, were randomly selected. Data pertaining to pain medications prescribed from the day of operation to sixth postoperative day were recorded. 180 prescriptions containing analgesics were collected randomly from the period of July 2007 to June 2008. In the operation day 65.6% patients received Nalbuphine and 33.3% patients received Pethidine. Along with Nalbuphine and Pethidine 86.7% patients received Tramadol and 13.3% patients received Ketorolac. 0.6% patients did not receive any analgesic in the day of operation. In 1st postoperative day, 84.4% patients received Ketorolac and 15.6% patients received Tramadol. In 2nd, 3rd, 4th and 5th postoperative day patients received Ketorolac 86.1%, 85.6%, 83.9% and 62.2% respectively. In 6th postoperative day, 92.8% patients did not receive any analgesics.DOI: 10.3329/bjpp.v25i1.5742Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 23-25